Renal Venous Stasis Index Reflects Renal Congestion and Predicts Adverse Outcomes in Patients With Heart Failure - Ohara, Himika; Yoshihisa, Akiomi; Horikoshi, Yuko; Ishibashi, Shinji; Matsuda, Mitsuko; Yamadera, Yukio; Sugawara, Yukiko; Ichijo, Yasuhiro; Hotsuki, Yu; Watanabe, Koichiro; Sato, Yu; Misaka, Tomofumi; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: It has been recently reported that the renal venous stasis index (RVSI) assessed by renal Doppler ultrasonography provides information to stratify pulmonary hypertension that can lead to right-sided heart failure (HF). However, the clinical significance of RVSI in HF patients has not been sufficiently examined. We aimed to examine the associations of RVSI with parameters of cardiac function and right heart catheterization (RHC), as well as with prognosis, in patients with HF. Methods: We performed renal Doppler ultrasonography, echocardiography and RHC in hospitalized patients with HF (n = 388). RVSI was calculated as follows: RVSI = (cardiac cycle time - venous flow time)/cardiac cycle time. The patients were classified to three groups based on RVSI: control group (RVSI = 0, n = 260, 67%), low RVSI group (0 < RVSI ≤ 0.21, n = 63, 16%) and high RVSI group (RVSI > 0.21, n = 65, 17%). We examined associations of RVSI with parameters of cardiac function and RHC, and followed up for cardiac events defined as cardiac death or worsening HF. Results: There were significant correlations of RVSI with mean right atrial pressure (mRAP; R = 0.253, P < 0.001), right atrial area (R = 0.327, P < 0.001) and inferior vena cava diameter (R = 0.327, P < 0.001), but not with cardiac index (R = -0.019, P = 0.769). During the follow-up period (median 412 days), cardiac events occurred in 60 patients. In the Kaplan–Meier analysis, the cumulative cardiac event rate increased with increasing RVSI (log-rank, P = 0.001). In the multivariate Cox proportional hazard analysis, the cardiac event rate was independently associated with RVSI (high RVSI group vs. control group: hazard ratio, 1.908; 95% confidence interval, 1.046–3.479, P = 0.035). Conclusion: RVSI assessed by renal Doppler ultrasonography reflects right-sided overload and is associated with adverse prognosis in HF patients.